A Comparative Study of the Effectiveness of Spiritual Therapy and Group Grief Counseling on the Experience of Grief for the Loss of a Loved One during the COVID-19 Period - Turkzadeh, Mohammad Hossein; Salah, Mohammad Mahdi; Agharahimi, Ayoub; Nobakht, Omid (Shahroud Journal of Medical Sciences, 2025)
Background: High-impact disasters, such as the COVID-19 pandemic, often lead to increased symptoms of grief disorders among those who have lost loved ones. This study aimed to compare the effectiveness of spiritual therapy and group grief counseling in managing the mourning process during the COVID-19 period. Methods: This study employed a quasi-experimental design, using a pre-test, post-test, and three-month follow-up approach with both control and experimental groups. The research population consisted of individuals in Tehran who experienced the loss of a family member due to COVID-19 between July and September 2020. A total of 37 participants were selected through convenience sampling. The intervention consisted of six sessions of group grief counseling and eight sessions of spiritual therapy facilitated by a clinical psychologist. Sessions were held twice a week in a group setting at one of the study’s clinics. Data were analyzed using the Kruskal-Wallis H test, repeated measures ANCOVA, and Bonferroni post hoc test, with a significance level of 0.05. Statistical analysis was performed using SPSS version 27 and JASP version 18.1.0. Results: The findings of this study revealed a significant difference (Pvalue<0.001) in the Between-Subjects Effects for the "Feeling Guilty" variable across both groups. Similarly, significant effects were observed in the Between-Subjects analysis for the components of "Trying to Justify and Get Along," "Feeling Left Out," and "Shame" (Pvalue<0.001). However, for the components "Physical Reactions" and "Judging Someone or Others," a significant interaction effect between time and group was found (Pvalue<0.05). Conclusions: The findings of this study indicate that both spiritual therapy and group grief counseling are effective in alleviating grief-related symptoms. However, spiritual therapy uniquely enhances the well-being of individuals grieving during the COVID-19 period by reducing feelings of guilt and providing a sense of justification through a connection to a higher power. Therefore, it is recommended that spiritual therapy, alongside psychotherapy, be considered for those mourning a loss during the COVID-19 pandemic.